The Acinetobacter baumannii model can explain the role of small non-coding RNAs as potential mediators of host-pathogen interactions - Sarshar, Meysam; Scribano, Daniela; Palamara, Anna Teresa; Ambrosi, Cecilia; Masotti, Andrea (Frontiers in Molecular Biosciences, 2022)
Bacterial small RNAs (sRNAs) research has accelerated over the past decade, boosted by advances in RNA-seq technologies and methodologies for capturing both protein–RNA and RNA–RNA interactions. The emerging picture is that these regulatory sRNAs play important roles in controlling complex physiological processes and are required to survive the antimicrobial challenge. In recent years, the RNA content of OMVs/EVs has also gained increasing attention, particularly in the context of infection. Secreted RNAs from several bacterial pathogens have been characterized but the exact mechanisms promoting pathogenicity remain elusive. In this review, we briefly discuss how secreted sRNAs interact with targets in infected cells, thus representing a novel perspective of host cell manipulation during bacterial infection. During the last decade, Acinetobacter baumannii became clinically relevant emerging pathogens responsible for nosocomial and community-acquired infections. Therefore, we also summarize recent findings of regulation by sRNAs in A. baumannii and discuss how this emerging bacterium utilizes many of these sRNAs to adapt to its niche and become successful human pathogen.